Effects of 8-week in-season plyometric training on upper and lower limb performance of elite adolescent handball players - Chelly, M. S.; Hermassi, S.; Aouadi, R.; Shephard, R. J. (The Journal of Strength and Conditioning Research, 2014)
We hypothesized that replacement of a part of the normal in-season regimen of top-level adolescent handball players by an 8-week biweekly course of lower and upper limb plyometric training would enhance characteristics important to competition, including peak power output (Wpeak), jump performance, muscle volume, and ball throwing velocity. Study participants (23 men, age: 17.4 ± 0.5 years, body mass: 79.9 ± 11.5 kg, height: 1.79 ± 6.19 m, body fat: 13.8 ± 2.1%) were randomly assigned between controls (C; n = 11) and an experimental group (E, n = 12). Measures preintervention and postintervention included force-velocity ergometer tests for upper (Wupper peak) and lower limbs (Wlower peak), force platform determinations of squat jump (SJ) and countermovement jump (CMJ) characteristics (jump height, maximal force, initial velocity, and average power), video filming of sprint velocities (first step [V1S], first 5 m [V5m], and 25-30 m [Vmax]), and anthropometric estimates of leg muscle volume. E showed gains relative to C in Wupper peak and Wlower peak (p < 0.01 and p < 0.001), SJ (height p < 0.01; force p < 0.05), CMJ (height p < 0.01; force p < 0.01 and relative power p < 0.05), and sprint velocities (p < 0.001 for V1S, V5m, and Vmax). E also showed increases in leg and thigh muscle volumes (p < 0.001), but arm muscle volumes did not differ from control. We conclude that introduction of biweekly plyometric training into the standard regimen improved components important to handball performance, particularly explosive actions, such as sprinting, jumping, and ball throwing velocity.